Effect of Reflective Journal Writing for Microteaching Implementations on Creative Thinking Tendencies of Primary School Teacher Candidates - Ahlatçıoğlu, Merve Elmas; Tekkol, İlkay Aşkın (IGI Global, 2024)
This study aims to reveal the effect of writing reflective journals about micro-teaching practices on the tendencies of creative thinking of primary school teacher candidates. This research was created using a mixed-methods approach. The research group for this study consists of third-grade students who attend a public university in Turkey with a primary school teaching program. A quasi-experimental design was employed in the quantitative part of the study, and a phenomenological design was utilized in the qualitative part of the study. According to the results, reflective journal writing for micro-teaching practices positively affected the creative thinking tendencies of primary school teacher candidates. In addition, primary school teacher candidates stated that reflective journal writing for micro-teaching practices developed creative thinking tendencies because they could think critically and gain different perspectives. When the qualitative data obtained from primary school teachers were evaluated, it was seen that they supported the quantitative data.